PELATIHAN KEGIATAN LITERASI DIGITAL UNTUK MENINGKATKAN KOMPETENSI GURU DI ERA KURIKULUM MERDEKA BELAJAR - Nurlaily, Vivi Astuti; Nafisah, Durrotun; Dayu, Dian Permatasari Kusuma; Cindy, Agustin Hanivia (Pusat Penelitian dan Pengabdian Masyarakat, 2024)
The Independent Curriculum is a new curriculum that requires the readiness of teachers and students to use technological information in implementing learning. Digital literacy can no longer be separated from learning in the current era. The aim of this community service is to prepare teachers to implement the Independent Curriculum, especially strengthening digital literacy. Before the training process, not all of the participants had digital literacy skills, so some teachers and students did not understand how to effectively use digital information media. Digital literacy training needs to be implemented because it is a practical solution for building digital literacy competencies for teachers in the independent learning curriculum. The results of the training showed that the teachers at SD Negeri Lakar Santri I Surabaya were very happy and satisfied taking part in the digital literacy training. Insight into the independent learning curriculum is increasing so teachers will continue to try to adapt to technology.